PHYSICAL ACTIVITY AND PERCEPTION OF WELFARE IN THE THIRD AGE (Fiep Bulletin - online, 2020)
The aging process brings with it numerous problems related to the fields, the environment in which they live, will bodily health, psychological and social. The ability of the elderly to maintain the quality of life and thus improve their general well-being is becoming increasingly precarious. However the implementation of activities to work these areas is critical to ensure improvement in the welfare of the elderly. For both this study aimed to investigate the difference in perception of well-being among a group of elderly advanced and another group of elderly people starting in physical activity, using the WHOQOL-BREF (1988) the World Health Organization, The overall sample was composed of twenty elderly subjects of both sexes. These twenty participants were divided into two groups: group 1 (advanced) and group 2 (beginner). The average age of the overall sample was 68.5 years. Regarding the perception of well-being (quality of life) to a group average was 72.09, whereas the second group received an average of 51.95. This indicates that the group of starters reached the lowest rate of perception d well-being in relation to the group of advanced physical activity.